Women’s empowerment in Rwandan agriculture: A baseline assessment in the context of Rwanda’s gender and youth mainstreaming strategy and the fourth strategic plan for agricultural transformation - Rosenbach, Gracie; Benimana, Gilberthe Uwera; Ingabire, Chantal; Spielman, David J.; Tumukunde, Ritha (International Food Policy Research Institute, 2023)
Rwanda is a recognized leader in the region and in the world in terms of women’s empowerment. However, no country has yet achieved full gender equality, resulting in untapped potential. The findings from the Women’s Empowerment in Agriculture Index (WEAI) baseline survey conducted in 2019 for the Ministry of Agriculture and Animal Resources (MINAGRI), indicated that women and men in Rwanda both have relatively high levels of empowerment across different agricultural do mains, and most women are as empowered as men in their households. This working paper dis cusses the findings further and in the context of MINAGRI’s Gender and Youth Mainstreaming Strategy that was also launched in 2019, as well as the Fourth Strategic Plan for Agricultural Transformation (PSTA 4). Key findings include the following. • Compared to other countries in the region, women in Rwanda have relatively greater access to financial services and a relatively lower time burden in agriculture. • However, when compared to men in Rwanda, inequalities persist. Women are significantly less likely than men to access financial services, participate in the marketing of agricultural commodities, access extension services, and spend their time on productive (rather than reproductive) work. By adapting and promoting innovative and gender-inclusive financial products, shifting gendered cultural norms, providing extension to both the household head and the spouse, and investing in time-saving technologies and innovations, there are opportunities to reduce the gender gap in agriculture and increase agricultural productivity. Realization of these outcomes will depend partly on the implementation of the Gender and Youth Mainstreaming Strategy and PSTA 4, and partly on coordination with other gender-transformative programs in Rwanda.